Service Quality Assessment Using Servqual and Kano Models - Kusuma Dewi, Shanty (Department Industrial Engineering, University of Muhammadiyah Malang, 2019)
The purpose of this study is to assess the quality of services by using the integration of Servqual and the Kano model. In this study, Servqual is used to determine the quality criteria that must be improved. At this method, the quality criteria are based on the gap that occurs between differences in perceptions and expectation of customers for the services they receive. Meanwhile, the Kano method is used to categorize service attributes that satisfy customer needs. Servqual integration and the Kano model were carried out by synchronizing the Servqual gap value and the Kano model grade. Assessment of service attributes obtained from both methods produces service attributes that will be the focus of management's improvement to improve service quality. The results showed that the attribute criteria that must be prioritized were attributes that included attractive and one-dimensional categories which had the highest negative gap value. Improvements in attributes in attractive and one-dimensional categories will improve service quality and increase customer satisfaction.